Development of Cooperative Web Cache Model - (NIM: 23507017); Pembimbing: Dr. Ir. Husni S. Sastramihardja, KATINI
This research develop modified cooperative web cache mode that has a wide range of object storage. The range of the object storage is calculated based on the optimal communication cost limit. The range of the object storage provide potential benefit of sibling hit caused by enhancement of web cache ability to save the web object. The range of the object storage also state the ability of cooperative web cache system to accomodate web object with a cheaper of cost communication, so can save the bandwidth. Therefore, the modified cooperative web cache model can be used as an alternative of the information technology strategy in ITB towards research university vision.